If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -5lnx = 6 Solving 8 + -5lnx = 6 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -5lnx = 6 + -8 Combine like terms: 8 + -8 = 0 0 + -5lnx = 6 + -8 -5lnx = 6 + -8 Combine like terms: 6 + -8 = -2 -5lnx = -2 Divide each side by '-5nx'. l = 0.4n-1x-1 Simplifying l = 0.4n-1x-1
| 5y+12=2-3 | | 0.5h+0.3(h-6)=0.30h+2 | | 44=5*-6 | | 11x=48 | | x/4-1=5 | | 7x+3-(3x+5)= | | x^3-2y^3+4x^3+3x^2y-2y^2+3y^3= | | (w+5)=2w^2+17w+35 | | (6-4x)-(x-9)= | | 23+3=67 | | 3x+12x=75 | | 8a-32-490= | | -2(2m-1)+4m= | | 8+2x=4x+4 | | -5mn^4+2mn-7= | | 7(49a+70)= | | -25=y+30 | | -17x=238 | | 8.8x=3.52 | | 7(3y)= | | 1.33+0.66x=2.93+1.2x+0.6 | | 6x^3-15x^2-9x=0 | | 4(2a-8)= | | 5(k-7)-k+7= | | 2.5x+0.5x=4x+9+3.5x | | 4(D+3)+7d= | | 4x+2y=y-2x+16 | | -10(y-5)= | | x^2-6x+59=0 | | X+2x+3x= | | 4(2y-1)= | | 10.71=1.7x |